2012
DOI: 10.1007/s11670-012-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F, MPL W515L and JAK2 exon 12 mutations in Chinese patients with primary myelofibrosis

Abstract: Objective: JAK2 V617F, MPL W515L and JAK2 exon 12 mutations are novel acquired mutations that induce constitutive cytokine-independent activation of the JAK-STAT pathway in myeloproliferative disorders (MPD). The discovery of these mutations provides novel mechanism for activation of signal transduction in hematopoietic malignancies. This research was to investigate their prevalence in Chinese patients with primary myelofibrosis (PMF).Methods: We introduced allele-specific PCR (AS-PCR) combined with sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Our data support the proposal of including JAK2 V617F, JAK2 exon 12, MPL exon 10, and CALR exon 9 mutations as the major diagnostic markers for MPN, given the findings from the data of our studies and others, that MPL exon 10 mutations were found only in ET and PMF, JAK2 exon 12 mutations were present only in JAK2 V617F-negative PV, and no CALR exon 9 mutation was identified in patients with PV. 16,17,22,23 While JAK2 V617F mutation is present in various types of MPN, patients harboring the MPL exon 10 or CALR exon 9 mutation should be excluded from the diagnosis of PV.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the proposal of including JAK2 V617F, JAK2 exon 12, MPL exon 10, and CALR exon 9 mutations as the major diagnostic markers for MPN, given the findings from the data of our studies and others, that MPL exon 10 mutations were found only in ET and PMF, JAK2 exon 12 mutations were present only in JAK2 V617F-negative PV, and no CALR exon 9 mutation was identified in patients with PV. 16,17,22,23 While JAK2 V617F mutation is present in various types of MPN, patients harboring the MPL exon 10 or CALR exon 9 mutation should be excluded from the diagnosis of PV.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of patients with PMF show the JAK3V617F tyrosine kinase mutation, also found in other myeloproliferative disorders (Zhang and Li 2008;Kiladijan 2012;Tibes et al 2012;Xia et al 2012;Milosevic and Kralovics 2013;Nielsen et al 2013). Among 30 patients with PMF, 50 % carried a JAK2V617F mutation (Xia et al 2012). The presence of the JAK2V617F mutation does not seem to have an impact on leukemic transformation in PMF (Helbig et al 2012).…”
Section: Cytogenetic and Molecular Featuresmentioning
confidence: 87%
“…No karyotype abnormality is proving the presence of PMF, but either del(13)(q12-22) or der (6)(1;6) is strongly suggestive (Hussein et al 2009). Approximately half of patients with PMF show the JAK3V617F tyrosine kinase mutation, also found in other myeloproliferative disorders (Zhang and Li 2008;Kiladijan 2012;Tibes et al 2012;Xia et al 2012;Milosevic and Kralovics 2013;Nielsen et al 2013). Among 30 patients with PMF, 50 % carried a JAK2V617F mutation (Xia et al 2012).…”
Section: Cytogenetic and Molecular Featuresmentioning
confidence: 98%
“…The frequency of JAK2 p. Val617Phe is 90-95% of patients meeting the clinical criteria for PV, 50-60% for ET, and 40-50% for PMF [5]. While JAK2 exon 14 mutation is the most frequent mutation in MPN, about 10% of patients with clinical characteristics of PV, ET, and PMF lack this mutation [5]. Somatic variants in exon 12 of JAK2 gene are found exclusively in PV patients and are detected in one third of PV patients who are p. Val617Phe negative [6].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic pathological variant in exon 14 of the JAK2 gene p. Val617Phe is the most associated mutation in BCR/ABL1-negative MPNs. The frequency of JAK2 p. Val617Phe is 90-95% of patients meeting the clinical criteria for PV, 50-60% for ET, and 40-50% for PMF [5]. While JAK2 exon 14 mutation is the most frequent mutation in MPN, about 10% of patients with clinical characteristics of PV, ET, and PMF lack this mutation [5].…”
Section: Introductionmentioning
confidence: 99%